2003
DOI: 10.1073/pnas.2134464100
|View full text |Cite
|
Sign up to set email alerts
|

An endogenous retroviral long terminal repeat is the dominant promoter for human β1,3-galactosyltransferase 5 in the colon

Abstract: LTRs of endogenous retroviruses are known to affect expression of several human genes, typically as a relatively minor alternative promoter. Here, we report that an endogenous retrovirus LTR acts as one of at least two alternative promoters for the human ␤1,3-galactosyltransferase 5 gene, involved in type 1 Lewis antigen synthesis, and show that the LTR promoter is most active in the gastrointestinal tract and mammary gland. Indeed, the LTR is the dominant promoter in the colon, indicating that this ancient re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 33 publications
1
109
0
2
Order By: Relevance
“…In competitive EMSAs (Fig. 6C), formation of the major complex was prevented by the addition of the HNF-1 binding sequence of the SIF3 oligonucleotide as well as by an antibody specific to HNF-1, indicating the presence of an HNF-1 binding site, as reported for the LTR promoter (6,7). To directly compare these two promoters, competitive EMSAs were performed using both sequences (Fig.…”
Section: Characterization Of the Promoter-driving Expression Of Type mentioning
confidence: 72%
See 2 more Smart Citations
“…In competitive EMSAs (Fig. 6C), formation of the major complex was prevented by the addition of the HNF-1 binding sequence of the SIF3 oligonucleotide as well as by an antibody specific to HNF-1, indicating the presence of an HNF-1 binding site, as reported for the LTR promoter (6,7). To directly compare these two promoters, competitive EMSAs were performed using both sequences (Fig.…”
Section: Characterization Of the Promoter-driving Expression Of Type mentioning
confidence: 72%
“…Type B and C 5Ј-UTR transcripts begin with exon 1B and 1C, respectively, and both comprise the two main splice variants described above. Exon 3 is present at the 3Ј-end of all of the novel 5Ј-UTR-containing transcripts, as is true for the LTR-and brain-derived 5Ј-UTR mRNAs (1,7).…”
Section: Identification Of Different 5ј-utrs In ␤3gal-t5 Transcripts-mentioning
confidence: 90%
See 1 more Smart Citation
“…An example is the carbonic anhydrase gene (CA1), where an ancestral LTR drives erythroid-specific expression of the orthologs [6]. The more commonly documented situation is where a lineage-specific LTR acts as a gene's promoter in one species but not the other, as illustrated by the b3GALT5 gene in human [31] and various mouse genes including Spindlin [32]. The results of this study illustrate a third evolutionary scenario not previously reported: distinct LTR elements specific to the primate or rodent lineages have independently assumed roles as promoters for the NAIP orthologs.…”
Section: Discussionmentioning
confidence: 99%
“…ORR1s and MTs are rodent-specific LTR families within the MaLR superfamily [24], represented by .400,000 copies in the sequenced mouse genome [2]. The fact that the ORR1E LTR is the primary promoter for these genes is unusual, considering LTRs most often function as tissue-specific or alternative promoters [7,8,31,32,37]. Another intriguing finding is the fact that an MTC LTR has inserted into the mNaipe/f progenitor and behaves as a secondary promoter.…”
Section: Discussionmentioning
confidence: 99%